Targeted delivery of irinotecan and SLP2 shRNA with GRP-conjugated magnetic graphene oxide for glioblastoma treatment. (17th May 2022) - Chuang, Chi-Cheng; Lan, Yu-Hsiang; Lu, Yu-Jen; Weng, Yu-Lun; Chen, Jyh-Ping
Abstract : Chitosan/urocanic acid modified mGO can anchor GPR, complex SLP2 shRNA and bind CPT-11 for dual targeted drug/gene delivery. Intravenous administration plus magnetic guidance provides excellent glioblastoma treatment in a murine brain tumor model. Abstract : Magnetic nanoparticles (MNPs) are useful for magnetic targeted drug delivery while ligand-mediated active targeting is another common delivery strategy for cancer therapy. In this work, we intend to prepare magnetic graphene oxide (mGO) by chemical co-precipitation of MNPs on the GO surface, followed by conjugation of the gastrin releasing peptide (GRP) as a targeting ligand, for dual targeted drug/gene delivery in invasive brain glioma treatment. mGO was grafted with chitosan, complexed with shRNA plasmid DNA for stomatin-like protein 2 (SLP2) gene silencing, modified with urocanic acid for plasmid DNA endosomal escape, PEGylated for GRP conjugation, and loaded with the chemotherapeutic drug irinotecan (CPT-11) by π–π interaction for pH-responsive drug release (mGOCUG/CPT-11/shRNA). In addition to the in depth characterization of the physico–chemical and biological properties during each preparation step, we also study the loading/pH-responsive release behavior of CPT-11 and the shRNA plasmid loading/cell transfection efficiency. The targeting and antitumor efficacies of the nanocomposite were studied with U87 human glioblastoma cells in vitro . An in vivo study revealed that intravenous administration followed by magnetic guidance results in the efficient targeted delivery of mGOCUG/CPT-11/shRNA to orthotopic brain tumors in nude mice, and it exhibits excellent antitumor efficacy with a reduced tumor growth rate and prolonged animal survival time. Our work thus highlights a multifunctional mGO-based drug/gene delivery platform for effective combination cancer therapy in glioblastoma treatment.